2013
DOI: 10.1515/cclm-2012-0704
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width is a potential prognostic index for liver disease

Abstract: RDW is a potential prognostic index for liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
66
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 17 publications
7
66
0
6
Order By: Relevance
“…It is hence noteworthy that, after the publication of the first study by Felker et al in 2007 [3], the number of papers about RDW as predictor of morbidity and mortality in health and disease has exponentially increased, with a mean raise of 27% per year (Figure 2). More recently, this journal has also published some original research that have further expanded the boundaries of potential clinical applications of RDW, for prediction of survival in patients with liver disease [9] and Eisenmenger syndrome [10], as well as for prognostication of chronic pulmonary hypertension in patients with acute pulmonary embolism [11]. A recent study published in this issue of the journal has also convincingly demonstrated that both gender and age are important determinants of Year Number of published items [3] Figure 2 Number of papers retrieved from the Scopus database using the keywords "red blood cell distribution width" or "RDW".…”
mentioning
confidence: 99%
“…It is hence noteworthy that, after the publication of the first study by Felker et al in 2007 [3], the number of papers about RDW as predictor of morbidity and mortality in health and disease has exponentially increased, with a mean raise of 27% per year (Figure 2). More recently, this journal has also published some original research that have further expanded the boundaries of potential clinical applications of RDW, for prediction of survival in patients with liver disease [9] and Eisenmenger syndrome [10], as well as for prognostication of chronic pulmonary hypertension in patients with acute pulmonary embolism [11]. A recent study published in this issue of the journal has also convincingly demonstrated that both gender and age are important determinants of Year Number of published items [3] Figure 2 Number of papers retrieved from the Scopus database using the keywords "red blood cell distribution width" or "RDW".…”
mentioning
confidence: 99%
“…11 In addition, RDW was found to be positively correlated with degree of cirrhosis based on Child-Pugh score and increased mortality of patients with coronary heart disease. 14,16 The mechanisms that can explain the condition until now is still unclear. Some elevation of pro-inflammatory cytokines, such as TNF-α, IL-1β (Interleukin-1β), and IL-6 (Interleukin-6), was suspected to be the cause of decreased levels of erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it is reported that systemic inflammation may cause an increase in RDW and it can be used as an alternative diagnostic inflammation and oxidative stress marker in many diseases such as CVD, renal diseases, thrombotic and hypertensive disorders [9,16] . Furthermore; Hu Z et al found increased RDW levels and showed RDW as a potential prognostic marker in different types of liver disease such as liver cirrhosis after HBV infection, primary hepatocellular carcinoma, and primary biliary cirrhosis [17].…”
Section: Discussionmentioning
confidence: 99%